Sleep quality, relationship functioning, and health-related quality of life in partners of CPAP-treated OSA patients - Giulia Marafioti; Enrica S. Vinci; Laura Culicetto; Viviana Lo Buono; Giovanni L. Cipriano; Rosalia Silvestri; Amelia Rizzo (Clinical Psychology in Europe, 2026)
Background Obstructive Sleep Apnea Syndrome (OSAS) is a chronic condition that negatively affects not only the patient but also the partner, influencing their sleep quality, psychological well-being, and couple relationship. However, scientific literature has given little attention to the partner's experience, especially regarding the impact of Continuous Positive Airway Pressure (CPAP) treatment on their partners’ health. The aim of the present study is to investigate sleep quality, couple relationship quality, and quality of life (QoL) in Italian-speaking partners of patients with OSAS treated with CPAP, compared to partners of healthy individuals. Method The study involved 100 participants, with a final sample of 48 partners of OSA patients and 49 partners of healthy subjects as a control group, assessed using the Pittsburgh Sleep Quality Index (PSQI), the Dyadic Adjustment Scale (DAS), and the SF-36 Health Survey. Statistical analysis included independent samples t -tests and Pearson’s correlations. Results Partners of patients with OSAS reported significantly poorer sleep quality (PSQI), lower levels of dyadic consensus and cohesion (DAS), and reduced perception of physical and mental health (SF-36) compared to the control group. Correlations revealed that sleep quality was negatively associated with relationship quality and perceived health, while years of relationship were positively associated with affection and cohesion, but negatively with sleep quality. Conclusions The findings confirm the interconnection between sleep quality and relationship functioning. A clinical approach that includes the partner in OSA treatment pathways may improve the overall well-being of the dyad.